Paleodiet in Western Idaho: An analysis of Mid-Archaic human remains from the Braden and DeMoss sites. (April 2016) - Pavesic, Max G.; Yohe, Robert M.; Owsley, Douglas W.; Camp-Hill, Amanda M.
Abstract: Two prehistoric archeological sites in western Idaho, the Braden and DeMoss sites, have produced numerous human remains dating to the Middle Holocene. As part of this study, the authors analyzed stable isotopes of carbon and nitrogen ( 13 C and 15 N) from collagen samples of these remains to reconstruct aspects of the diets of these individuals. Carbon isotope values (δ 13 C‰) from Braden range between − 14.47 and − 16.84; those from the DeMoss ranged between − 19.10 and − 19.13. Nitrogen values (δ 15 N‰) ranged between 13.7 and 18.1 Braden and between 9.13 and 9.44 at DeMoss. These results indicate that salmon played a vital dietary role for the peoples represented at Braden, whereas individuals living at DeMoss relied on a mixed terrestrial diet. Differences in these subsistence patterns are also suggested by analysis of dental calculus and pathology. Highlights: This paper provides data relating to various analyses of human skeletal material from two important Western Idaho Archaic Burial Complex (WIABC) cemeteries: The Braden and DeMoss sites. These analyses include delta 13 C and 15 N ratios, dental calculus paleobotanical contents from the DeMoss samples, and the incidence of caries in both populations in an effort to reconstruct mid-Holocene diets near the Plateau/Great Basin interface. The isotopic data from the Braden site, located on the Snake River in western Idaho and dating to 7, 500 CalBP, indicates that the individuals in sample (n = 17) subsisted on a diet high in salmon, with isotopic values equivalent to marine mammals. The same isotopic data from the DeMoss sample suggests more of a mixed terrestrial diet with little or no dependence on anadromous fish. Additional data provided by fiber, pollen, and starch grains extracted from the dental calculus of 10 teeth from the DeMoss site indicates the inclusion of grass seeds and starchy roots, such as camas ( Camassia quamash ), in the diet. The occurrence of dental caries in both populations is higher than generally seen in hunter/gatherer populations. The overall incidence of carious lesions in the teeth of both populations may be related to the reliance on pit-roasted camas.